Зависимость сопротивления металлических квантовых проводов от температуры - Obukhov, I. A. (PE "Politekhperiodika", Book and Journal Publishers, 2007)
An explanation is given for the experimentally observed changes in the temperature dependence of resistance in metallic quantum wires when their transverse size is varied. The unusual behavior of resistance can be explained by taking into account the injection of electrons from the contact regions into the conducting channel of the quantum wire.